Images of women breastfeeding in public: solitude and sociality in recent photographic portraiture - Fiona Giles (BMC, 2018)
Abstract Contemporary images of women breastfeeding - from breastfeeding selfies to fine art - celebrate breastfeeding outside the home by displaying visual records of these occasions to a wider audience. From brelfies posted by celebrities and ordinary parents on social media, to the photography of Tara Ruby and Ivette Ivens, media coverage of lactivist nurse-ins, or fine-art works by Ashlee Jenkins and Sky Boucher, the repertoire of breastfeeding images in developed Western nations has grown and diversified exponentially in the past ten years. A subject that was once the province of religious painting, ethnography, public health advocacy or obscure corners of pornography, is increasingly made visible within the everyday, not only through self-portraiture on social media but also through the work of celebrated photographers and visual artists. Despite this, there is still an absence of images of women breastfeeding in social circumstances, suggesting a reluctance to make the leap from understanding breastfeeding as a solitary activity, regardless of the space the mother inhabits at the time, to a companionable behaviour integral to our social landscape. Images predominate of women breastfeeding alone, or at best with other breastfeeding women, revealing a further binary dividing the acceptable from the unacceptable, where the private vs. public has been conflated with the solitary vs. social. This article provides a textual analysis of contemporary photographic portraiture to interpret the meanings of key works, and their patterns of signification. It asks to what extent these images advance efforts to normalize breastfeeding and make it publicly commonplace, or reinforce unhelpful binaries, using an iconography based on the religious origins of portraiture itself: the virtuous, devoted mother, unaccompanied but for her child. I conclude that the lack of images where breastfeeding women are integrated into social occasions is partly due to the lack of opportunities for women to breastfeed socially, and few motives for these instances to be recorded, and that there is an unspoken proxemics of viewing space yet to be traversed.